WEB-BASED LAWYER INFORMATION SYSTEM DESIGN AT NURHADISIGITLAW OFFICE - Mohammad Syamsul Aziz (Universitas Islam Kuantan Singingi, 2021)
The presence of information systems today can be felt by almost all elements of society. In the elements of government, education, public and private industry, even UMKN has started to use information systems in carrying out their activities. The development of information system technology has not fully touched the current field, one of them is the element of the profession as a lawyer. In the 4.0 revolution era, lawyers should use a website-based information system. This is done to make easy for clients to get information quickly and accurately. Making information systems using the waterfall method can run effectively, because it has phase of system requirements analysis, design, coding, and testing. With the support of the HTML, PHP, Javascript, and CodeIgniter programming languages ​​so that the process of creating a lawyer information system at NurhadiSigit Law Officer runs as expected and can be implemented optimally.